Maintenance Electroconvulsive Therapy Is an Essential Medical Treatment for Patients With Catatonia: A COVID-19 Related Experience - Ghaziuddin, Neera; Yaqub, Tareq; Shamseddeen, Wael; Reddy, Priyanka; Reynard, Hannah; Maixner, Daniel (Frontiers in Psychiatry, 2021)
Aim: Describe naturalistic clinical course over 14 weeks in a mixed adolescent and a young adult patient group diagnosed with catatonia, when the frequency of maintenance electroconvulsive therapy (M-ECT) was reduced secondary to 2020 COVID-19 pandemic restrictions. Methods: Participants were diagnosed with catatonia, and were receiving care in a specialized clinic. They were (n = 9), F = 5 and M = 4, age range in years = 16 to 21; ECT frequency was reduced at end of March 2020 due to institutional restrictions secondary to the pandemic. Two parents/caregivers elected to discontinue ECT due to concern for COVID-19 transmission. Majority (n =8) were developmentally delayed with some degree of intellectual disability (ID). Observable symptoms were rated on a 3-point scale during virtual visits. Results: All cases experienced clinically significant decline. Worsening of motor symptoms (agitation, aggression, slowness, repetitive self-injury, stereotypies, speech deficits) emerged within the first 3 weeks, persisted over the 14 week observation period and were more frequent than neurovegetative symptoms (appetite, incontinence, sleep). Four participants deteriorated to the point of requiring rehospitalization and 2 among these 4 needed a gastrostomy feeding tube. Conclusion: Moderate and severe symptoms became apparent in all 9 cases during the observation period; medication adjustments were ineffective; resuming M-ECT at each participant’s baseline schedule, usually by week 7, resulted in progressive improvement in some cases but the improvement was insufficient to prevent re-hospitalization in 4 cases. Our findings underscore that M-ECT is an essential medical procedure for this select patient group.